Physical demands and physiological responses of extra time matches in collegiate women's soccer - Williams, J. H.; Hoffman, S.; Jasko.; Jaskowak, D. J.; Tegarden, D. (Science and Medicine in Football, 2019)
Purpose: In U.S. collegiate soccer, matches that end drawn after 90-min of regulation time (RT) proceed to two 10-min extra time (ET) periods. This study quantified the physical demands and heart rate (HR) responses of playing ET matches in women's collegiate soccer matches and compared performances during ET to those of RT.